COMMD4 is a novel prognostic biomarker and relates to potential drug resistance mechanism in glioma - Liu, Zongheng; Peng, Long; Sun, Yidan; Lu, Zhichao; Wu, Bing; Wang, Weichen; Zhang, Xiaomei; Hao, Haiyan; Gong, Peipei (Frontiers in Pharmacology, 2022)
Glioma is the most frequent tumor affecting the brain with significant morbidity and fatality rates and patients' prognoses are still dismal. There is an urgent necessity to find novel therapeutic targets considering the low chemotherapeutic efficacy for this disease. This research intended to examine whether the copper-metabolism-domain protein, COMMD4, has any predictive and therapeutic significance in glioma. Using the freely accessible CGGA (The Chinese Glioma Atlas) and TCGA (The Cancer Genome Atlas) databases, we examined the function of COMMD4 in GBM and LGG. CIBERSORT and TIMER were utilized to assess the associations between COMMD4 and immune cells. The Gene Set Enrichment Analysis (GSEA) was executed to examine the functional data. Furthermore, the link between COMMD4 expression and predicted treatment response was evaluated via CellMiner Cross-Database. Finally, qRT-PCR was undertaken to examine COMMD4 expression in human glioma. R was used to analyze the statistical data.COMMD4 expression level was found to be greater in patients having grade-dependent glioma who had a dismal prognosis, according to our findings. Additionally, using integrated correlation analysis, we acquired significant prognostic findings between isocitrate dehydrogenase 1(IDH1) and COMMD4. Meanwhile, we discovered a link between COMMD4 and many tumor-infiltrating immune cells. Furthermore, GSEA and drug response analysis reveal the potential mechanism of COMMD4 in drug resistance in glioma. In light of these findings, the discovery of COMMD4 as a novel biological marker might offer insights into the possible drug resistance mechanisms as well as the impact of the immune microenvironment in glioma. COMMD4 might be used to predict glioma prognosis with further analysis.